Monocyte to High-Density lipoprotein and Apolipoprotein A1 Ratios: Novel Indicators for Metabolic Syndrome in Chinese Newly Diagnosed Type 2 Diabetes - Wang, Wei; Chen, Zhe Yuan; Guo, Xiu Li; Tu, Mei (Frontiers in Endocrinology, 2022)
Objective: Increasing evidences highlighted that chronic inflammation involved in the development of metabolic syndrome (MetS) and type 2 diabetes(T2DM). This prospective study was aimed to assess the association between MetS and novel pro-inflammatory indicators like monocyte to high density lipoprotein and apolipoprotein A1 ratios (MHR and MAR) in Chinese newly diagnosed T2DM. Method:A total of 605 Chinese newly diagnosed T2DM with complete and available data were enrolled in this study. Demographic and anthropometric information were collected. Laboratory assessments were determined by standard methods. MetS was based on the Chinese Diabetes Society definition. Multiple binomial logistic regression model was used to estimate the independent variables of MHR and MAR for MetS. Receiver operating characteristic (ROC) curve was conducted to assess the optimal cutoff value of MHR and MAR in identifying MetS. Results: Overall, the prevalence of MetS was 60.2%. The correlation analysis showed that MHR and MAR were closely correlated with metabolic risk factors like body mass index, waist circumference, triglycerides, high-density lipoprotein cholesterol, systolic blood pressure, diastolic blood pressure, uric acid, and insulin resistance. MHR and MAR were also significantly associated with higher odds of MetS after adjustment for other confounders, the ORs(95%CI) were 1.50(1.14-1.97) and 2.26(1.79-2.87) respectively. Furthermore, MHR and MAR were also seem to have higher AUC for MetS than APOA1 and monocyte alone from the ROC curve analysis (P<0.05). The areas under the curve of MHR and MAR identifying MetS were 0.804 (95% CI: 0.768-0.839) and 0.840 (95% CI: 0.806-0.873) respectively( P< 0.001).The optimal cut-off values of MHR and MAR were 3.57x108/mmol (sensitivity: 76.1%, specificity: 73.4%) and 3.95x108/g (sensitivity: 79.7%, specificity: 84.6%) respectively. Conclusions: MHR and MAR were significantly associated with MetS. These two novel pro-inflammatory indicators may be useful markers for MetS in Chinese newly diagnosed T2DM.